Deep Learning Powered Secure Distributed Systems for Financial Analytics, Healthcare Monitoring, and Smart Infrastructure (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
The rapid digitization of modern industries has led to an unprecedented growth in data generated across financial institutions, healthcare ecosystems, and smart infrastructure networks. This data is often distributed, heterogeneous, and sensitive in nature, requiring advanced analytical models combined with robust security and privacy-preserving mechanisms. Deep learning powered secure distributed systems have emerged as a transformative paradigm capable of addressing these challenges by integrating intelligent analytics, decentralized computing architectures, and cryptographic safeguards. This research explores the design, implementation, and evaluation of secure distributed systems that leverage deep learning to enable scalable financial analytics, real-time healthcare monitoring, and resilient smart infrastructure management. In financial analytics, deep learning models deployed across distributed ledger technologies and edge-cloud infrastructures facilitate fraud detection, credit risk modeling, algorithmic trading, and anomaly detection while preserving transactional privacy. Techniques such as federated learning and secure multiparty computation allow institutions to collaboratively train models without exposing raw financial data. In healthcare monitoring, distributed systems integrate wearable sensors, IoT devices, and hospital databases to provide predictive diagnostics, early disease detection, and remote patient monitoring, while maintaining compliance with regulatory frameworks like HIPAA and GDPR. Privacy-preserving mechanisms such as homomorphic encryption and differential privacy ensure secure data exchange across medical networks. Smart infrastructure applications—ranging from intelligent transportation systems to smart grids—rely on distributed sensor networks and edge computing nodes. Deep neural networks deployed at the edge enable low-latency decision-making for traffic optimization, energy load balancing, and structural health monitoring. Blockchain-based consensus mechanisms enhance trust, transparency, and data integrity across decentralized infrastructure systems. This research proposes a unified architecture that integrates deep neural networks, distributed computing frameworks, and advanced cryptographic protocols to build scalable, resilient, and secure systems. The study evaluates performance metrics including accuracy, latency, scalability, fault tolerance, and privacy guarantees. Experimental simulations demonstrate significant improvements in model robustness and operational efficiency while maintaining strong security assurances. The findings highlight the potential of deep learning powered secure distributed systems as a foundational technology for next-generation digital ecosystems, enabling trustworthy AI-driven analytics across finance, healthcare, and smart infrastructure domains.
Keywords: Deep Learning; Secure Distributed Systems; Financial Analytics; Healthcare Monitoring; Smart Infrastructure; AI-Driven Platforms; Cloud-Native Systems; Predictive Analytics